2015
DOI: 10.1097/scs.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Buccal Fat Pad as Free Graft for Closure of Oronasal Fistula in a Cleft Palate Patient

Abstract: Oronasal fistulas are frequent complications after cleft lip and palate surgery, with difficult treatment because of the presence of fibrotic and scarred tissue as well as the absence of local virgin tissue, representing a challenge in oral and maxillofacial surgery. The size of the fistula, its location, and the cause of the defect are important factors to determine the type of treatment and surgical technique. The use of pedicled buccal fat pad (BFP) for the repair of cleft palate has shown promising results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…In separate articles, previous studies reported a complete epithelialization period of 4–6 weeks ( 1 , 3 , 5 - 8 ). The fast healing process in this BFP graft was associated to the progression of epithelialization ( 1 , 5 , 9 ). This process possibly come from rich blood supply and fresh wound around the defect ( 1 , 8 , 9 , 12 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In separate articles, previous studies reported a complete epithelialization period of 4–6 weeks ( 1 , 3 , 5 - 8 ). The fast healing process in this BFP graft was associated to the progression of epithelialization ( 1 , 5 , 9 ). This process possibly come from rich blood supply and fresh wound around the defect ( 1 , 8 , 9 , 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…Since Indonesia - as a developing country - has a considerable amount of low economic population with poor oral hygiene maintenance, this can lead to a serious and possibly fatal complication over the result of conventional palatoplasty procedure such as infection, wound dehiscence, risk of fistula, scarring, hematoma and partial necrosis ( 5 , 9 , 10 ). Due to this fact, one of the main consideration when planning surgical procedures using BFP as pedicled graft in our cases is the excellent healing of BFP with minimal complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even when a non-pedicled graft was used, as reported in the third clinical case, there was excellent tissue stability, and local vascularization was also provided by the palatal flap. Satisfactory results were also found in free grafts for treatment of patients with cleft lip and palate in the anterior region of maxilla [16] .…”
Section: Discussionmentioning
confidence: 76%
“…Depending on the type of surgical procedure performed, the rate of fistula occurrence has been reported to be 4.9% (Bykowski et al, ) or up to 17.7% (Kahraman et al, ). These techniques range from the use of a pedicle buccal fat pad (BFP; de Castro, de Souza, & Fernandes Santos, ), conchal cartilage graft to repair large fistula (Funayama et al, ), multilayered repair of the whole palate (Funayama et al, ), or a tri‐layered repair where the bone and cartilage are harvested from the nasal septum of the same patient and are used to create the middle layer sandwiched between two vascular layers (Hudson & Pickett, ).…”
Section: Introductionmentioning
confidence: 99%